Physiological profiles of elite senior wrestlers - Yoon, J. (Sports Medicine, 2002)
To perform excellently in international competitions, wrestlers have to achieve an excellent level of physical fitness and physical condition during training. This article reviews the physiological profiles of elite wrestlers. In general, successful wrestlers showed higher dynamic and isokinetic strength than unsuccessful wrestlers. In particular, upper body strength and anaerobic power were significantly different between the two groups.